Effect of fixed orthodontic appliances on gingival status and oral microbiota: a pilot study - Zuzana Marincak Vrankova; Margarita Rousi; Michaela Cvanova; Daniela Gachova; Filip Ruzicka; Veronika Hola; Jan Lochman; Lydie Izakovicova Holla; Alena Brysova; Petra Borilova Linhartova (BMC, 2022)
Abstract Background This pilot study aimed to investigate how fixed orthodontic appliances simultaneously applied on the upper and lower arches affect the oral environment in the medium term. Methods The oral status of 30 orthodontic patients was evaluated using the number of decay-missing-filled teeth (DMFT), plaque (PI), and gingival indices (GI) before bonding of fixed orthodontic appliances (T0) and during the therapy (T1). Besides, the gingival crevicular fluid (GCF) and a dental plaque were collected. Samples were analyzed for selected Candida sp. and for 10 selected oral bacteria using mass spectroscopy and multiplex polymerase chain reaction, respectively. Results In 60% of patients, deterioration of the oral status (demonstrated by the increase in PI) was recorded (p < 0.05). Moreover, the changes in PI correlated with those of GI (p < 0.001). At the T1 time point, the mean representation of Actinomyces sp. in the total prokaryotic DNA in GCF and dental plaque of individual patients increased compared to T0 (p < 0.05). The probability of finding any of the 7 selected periodontal bacteria combined with Candida sp. was 10 times higher in patients in whom PI deteriorated between T0 and T1 (p < 0.01). Conclusions Changes in the oral microbial diversity and an increase in PI were observed in the medium term after bonding of orthodontic appliance. Our study highlights the importance of a complex approach in this type of research as the association between clinical characteristics and combined microbial parameters is higher than when evaluated separately.